To change banks or bankers? Systemic political (in)action and post-crisis banking reform in the UK and the Netherlands. (March 2020) - Ganderson, Joseph
Abstract: After the subprime financial crisis, the countries who were worst affected set about reforming legacy financial regulations. Given multiple similarities in the way they experienced the crisis and the similar complexions of their post-crisis economies and politics, the contrast between the UK and the Netherlands' approaches to breaking up their largest banks presents a puzzle for prevailing theories in the politics of financial regulation. Both countries explored a range of reform options using similar expert committees, but while UK policymakers determined that commercial and investment operations should be ring-fenced in the largest British banks, the Dutch reform program centered on the banks' own recommendations to change banking culture from the bottom up by developing a code of conduct and banker's oath. The paper traces this divergence to two related effects produced by the countries' contrasting majoritarian and consensus party systems: power sharing and coalition formation. Under conditions of high issue salience, both worked to encourage British policymakers to prioritize reform, while in the Netherlands each factor reduced party political responsiveness and de-emphasized alternatives to the banks' own reform prescriptions. The paper ultimately suggests that institutional democratic variables are worthy of greater recognition among scholars of business power and financial regulation.